L'enseignement de l'EPS comme espace de bien-être relationnel - Emmanuel Fernandes; Iman Nefil; Sébastien Calais; Célia Yakoubi
The objective is to identify if teaching contexts (in maths, French and Physical Education) influence pupils' social representations. Social representations are prerequisites for social relations and actions. Are they more favourable in PE? The results show that the egocentration of schoolchildren is opposed to the suffered exocentration by high school students. Boys' positive emotional exocentration contrasts with girls' negative emotional self-centration. In PE, the representations would reflect a relational well-being. In Maths, the representations reflect a stereotyped rigour of pupils frozen by the mathematical operations to be performed. In French, the representations reflect a relational malaise and a rejection of this discipline. These students seem to live in an oppressive and boring context until they enter the heart of their imagination. It would be mainly the impregnation of the teaching context that would influence the students' representations.